Exploring Barrier-Free Esports for Visually Impaired and Sighted Individuals: An Examination of Rapid Key Tapping Speed - Miyono Okinaka; Tsunehiko Wada (Disabilities)
Esports involves competition conducted through online computer games, a format that allows individuals to compete together regardless of age, sex, or physique. However, due to preconceived notions about individuals with visual impairments, their abilities are occasionally underestimated or overestimated. Furthermore, while esports heavily depend on visual elements, there has been little clarification on which abilities can be performed equally by both sighted and visually impaired individuals and which abilities differ. This study examined whether rapid tapping speed, a skill potentially utilized in esports, is affected by visual impairment, testing the hypothesis that there is no significant difference in tapping speed between visually impaired and sighted individuals. By identifying skills that show no differences and those that do, this research lays the groundwork for designing environments where all participants can equally enjoy activities, including the appropriate use of handicaps. The study employed a 30 s rapid tapping speed evaluation model in which participants were asked to tap a key on a computer keyboard as quickly as possible. The total number of taps, initial speed, and speed maintenance were measured over three trials, and temporal changes, such as deceleration, were assessed. No significant differences were observed between groups in the total number of taps, initial speed, or speed maintenance, indicating that tapping speed is not dependent on visual impairment. Thus, a rapid tapping ability can be equally demonstrated by both visually impaired and sighted individuals, highlighting the potential for increasing inclusivity in esports. These findings highlight the potential for creating inclusive esports environments that accommodate visually impaired players, thereby promoting broader participation.